Exploring solvatochromism in Nile Blue 690 dye: Evaluating dipole moments across the ground and excited states - Hirematada, Darukaswamy Tulahalli; Patil, Mallikarjun Kalagouda; Inamdar, Sanjeev Ramchandra; Goudar, Kotresh Mare (European Journal of Chemistry, 2024)
This study investigates the photophysical properties of Nile Blue 690 (NB-690) dye using spectroscopic techniques. Absorption and fluorescence spectroscopy were used to analyze NB-690, revealing pronounced bathochromic shifts in both absorption and fluorescence spectra, indicative of the π → π* transition. The study focuses on estimating ground- and excited-state dipole moments of NB-690 through solvatochromic shifts in absorption and fluorescence spectra. Various computational methods, including the Bilot-Kawski approach for ground state dipole moment computation, and the Reichardt correlation, the Bakhshiev, the Lippert-Mataga, and the Kawski-Chamma-Viallet methods for calculating the excited state dipole moment, were utilized. The results demonstrate excited-state dipole moment values of 6.922, 5.529, 5.529, 5.529, and 4.615 D, respectively, using the Lippert-Mataga, Bakhshiev, Kawski-Chamma-Viallet and solvent polarity correlation approaches. Significantly, the excited state dipole moment surpasses the ground state dipole moment, attributed to the significant π-electron density redistribution upon excitation. Intriguingly, both excited- and ground-state dipole moments align parallel to each other at a 0° angle. In general, these findings underscore the potential utility of NB-690 in optoelectronic applications, highlighting its responsiveness to environmental signals and providing valuable information for further exploration in the field.